(untitled) (Scientific journal of the Fergana State University, 2023)
The most studied of the oil acids in the article are naphthenic acids, which are present in all components of the oil. It is important to isolate them from the composition of oil fractions and study their properties. Silica gel with a pore radius of 70 A0 and alumina are very active towards the oxygen-containing components of oil (phenol, fatty and naphthenic acids), but they also adsorb the hydrocarbon part of the fuel in small amounts. Consequently, when isolated with these sorbents, naphthenic acids will contain about 10% hydrocarbon impurities. In order to avoid additional technological processes for the purification of naphthenic acids from hydrocarbons, it is better to use the most coarse-pored silica gel, with a pore radius of 300 A0. The most studied of the petroleum acids are naphthenic acids, which are found in all components of oil. It is important to separate them from oil fractions and study their properties.